Characterization of an experimental two-step self-etch adhesive’s bonding performance and resin-dentin interfacial properties - Abu Faem Mohammad Almas Chowdhury (2022)
This study evaluated an experimental two-step self-etch adhesive (BZF-29, BZF) by com-paring it with a reference two-step self-etch adhesive (Clearfil Megabond 2, MB) and a universal adhesive (G-Premio Bond, GP) for microtensile bond strength (µTBS) and resin-dentin interfacial characteristics. Twenty-four human third molars were used for the µTBS test. Bonded peripheral dentin slices were separated to observe the resin-dentin interface and measure the adhesive layer thickness with SEM. µTBS data of the central beams were obtained after 24 h and 6 months of water storage. Fracture modes were determined using a stereomicroscope and SEM. Nine additional third molars were used to determine the elastic modulus (E) employing an ultra microhardness tester. Water storage did not affect µTBS of the tested adhesives (p > 0.05). µTBS of BZF and MB were similar but significantly higher than GP (p < 0.05). BZF achieved the highest adhesive layer thickness, while GP the lowest. E of BZF and MB were comparable but significantly lower than GP (p < 0.05). Except for GP, the predominant fracture mode was nonadhesive. The superior bonding performance of BZF and MB could be attributed to their better mechanical property and increased adhesive thickness imparting better stress relief at the interface.